1969
DOI: 10.1021/es60034a006
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of manganese, iron, phosphorus, magnesium, potassium, sodium, and calcium in the surface sediments of Lake Mendota, Wisconsin

Abstract: Analysis of 32 surface sediment samples from different areas of Lake Mendota, Wis., indicated a high positive statistical correlation between Mn, Fe, and P concentration in the sample and the depth of water overlying the point of sample recovery. An inverse correlation was found for Mg and K. No statistical correlation between concentration and depth of sample recovery was found for Ca and Na. urface sediment samples were collected from Lake S Mendota, Wis., during the summer and early fall of 1967.The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…However, for Mg the comparable statistics were only 0.5 ± 0.3 mg L™1, or 2% of the epilimnetic mean. On the basis of these results and independent sedimentary evidence (21)(22)(23), Mg acts conservatively (F = F' = 0) in these study lákes. Calcium is also conservative in soft-water lakes of the Northern Highlands.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…However, for Mg the comparable statistics were only 0.5 ± 0.3 mg L™1, or 2% of the epilimnetic mean. On the basis of these results and independent sedimentary evidence (21)(22)(23), Mg acts conservatively (F = F' = 0) in these study lákes. Calcium is also conservative in soft-water lakes of the Northern Highlands.…”
Section: Resultssupporting
confidence: 73%
“…In humid regions with abundant dolomite, Mg offers advantages over Ca as a tracer because, once in solution, it does not re-form a carbonate in lakes unless Mg/Ca > 2 (20). This geochemical distinction accounts for the very high CaO/MgO ratios in lake sediments of southeast Wisconsin (21,22) and elsewhere (19,23). Because Mg behaves nearly conservatively within the lake water column, only a few measurements will suffice to estimate C0' and C¿ for individual study lakes.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…On the basis of statistical analysis of 35 sediment samples, Delfino et al (33) concluded that Mn and P were much more closely related in recent Mendota sediments than Fe and P. Because of the long-known association between Fe and P in certain environments undergoing redox shifts (cf. 2,36,50), this Mn-P "association" has been labeled a statistical "artifact" (57).…”
Section: Discussionmentioning
confidence: 99%
“…This application of "ratio estimation" (cf. 35) depends on the close geochemical association among Fe, Mn, and P in the postcultural sludge sediments (called gytta) in Mendota (33). Annual losses of Mn and Fe at the outlet were computed based on seasonal discharge (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the morphological and hydrophysical characteristics of lakes and marine basins, redox changes may cause a spatial redistribution of particulate Mn in lakes (Delfino et al 1969;Ostendorp and Frevert 1979;Schaller and Wehrli 1996;Dellwig et al 2018) and marine basins (Rajendran et al 1992;Lenz et al 2015a, b;Häusler et al 2018;Schaller and Wehrli 1996) introduced the term ''geochemical focusing'' to address the mobilisation of Mn from shallow sediments, its transportation within the water column, and sedimentation in the deep zones of lakes. In marine geology and sedimentology, the term ''shelf-to-basin shuttle'' is more common for this transport process (Lyons and Severmann 2006;Scholz et al 2013).…”
Section: Introductionmentioning
confidence: 99%